Effect of briquetting pressure on combustion properties of hydrothermally treated king grass biomass - Alchalil, Alchalil; Setiawan, Adi; Dirga, Muhammad; Riskina, Shafira; Nurjannah, Siti; Hasibuan, Rizqon; Rahman, Abdul (Politeknik Negeri Lhokseumawe, 2025)
The utilization of biomass as an alternative energy source continues to gain attention, particularly in the form of solid briquettes with properties comparable to coal. In Indonesia, the co-firing program in coal-fired power plants (PLTU) promotes the use of biomass briquettes as supplementary fuel. King grass (Pennisetum purpureum), a fast-growing, non-food crop that thrives on marginal land, is a promising candidate. However, its low energy density limits practical application. This study aims to enhance the fuel quality of king grass through hydrothermal treatment and evaluate the effect of varying briquetting pressures on briquette properties. Briquettes were produced without pressure and with compaction pressures of 100, 200, 300, 400, and 500 kg/cm². Results show that higher briquetting pressure reduced moisture content from 3.99% to 2.98% and friability from 54.46% to 11.95%. While ash content and volatile matter were minimally affected, fixed carbon increased to 28.42%, and calorific value peaked at 3,923 kcal/kg. Hydrothermal treatment further improved calorific value, reduced ash content, and enhanced fixed carbon levels. These findings demonstrate that the combination of hydrothermal treatment and briquetting pressure significantly improves king grass briquette quality, supporting their potential as a sustainable co-firing fuel in coal-fired power plants.